Acute effect of low-dose sugar ingestion on forearm blood flow in healthy men - Korakot, Manta; Kositanurit, Weerapat; Varachotisate, Pachara; Burana, Chuti; Boonla, Chanchai; Kulaputana, Onanong (Chulalongkorn Medical Journal, 2022)
Background: Hyperglycemia is a major risk factor for cardiovascular disease resulting in vascular damage in both diabetic and non-diabetic people. Objective: To determine acute effect of elevated plasma glucose from a low-dose sugar ingestion on forearm blood flow (FBF) in healthy men. Methods: Ten healthy men (aged 24.1 4.1 years) participated in two experimental conditions: 1) drinking 200 mL of water (Control), and 2) drinking 15 grams of sugar solution (Sugar). The two conditions were scheduled in random order with a minimum of three days of washout period between conditions. FBF was determined by venous occlusion plethysmography. Peak forearm blood flow (FBFpeak) and area under the curve of forearm blood flow (FBFAUC) during reactive hyperemia were obtained before and every 30 minutes after sugar ingestion for 2 hours. Plasma glucose and serum insulin levels were measured before and 30, 60, and 120 minutes after sugar/ water ingestion. Results: In the Sugar, FBFpeak at 30 minutes significantly decreased when compared to baseline, 90 and 120 minutes (P < 0.05 for all comparisons). Comparing to the Control, FBFpeak at 30 minutes also significantly decreased (P < 0.0001). FBFAUC at 30 minutes slightly but insignificantly decreased from baseline after sugar ingestion. Plasma glucose and serum insulin levels significantly increased at 30 minutes after sucrose ingestion and returned toward baseline afterward. Conclusion: In healthy persons, a low amount of sugar ingestion acutely impairs vasodilating function. Decreased FBFpeak parallels with the elevation of plasma glucose and insulin responses after sugar ingestion.